Tunable absorber embedded with GST mediums and trilayer graphene strip microheaters - M. Pourmand (Nature Portfolio, 2021)
Abstract Investigation was made of the optical response of metal-dielectric stacks-based cavity structures embedded with graphene microheaters for the purpose of perfect absorption. The absorber configuration exploits the Ge2Sb2Te5 (GST) phase changing medium, and the effects of different parametric and operational conditions on the absorption spectra were explored. The refractive indices of GST layers can be manipulated by the external electrical pulses applied to microheaters. The amplitude and duration of electrical pulses define the crystallinity ratio of the used GST mediums. The results revealed achieving perfect absorption (> 99%) in the visible and infrared (IR) regimes of the electromagnetic spectrum upon incorporating two thin GST layers of different thicknesses (in the stack) in the amorphous state. The proposed configuration showed the capability of introducing independent transition state (amorphous and/or crystalline) for each GST layer—the visible regime could be extended to the IR regime, and the perfect absorption peak in the IR regime could be broadened and red-shifted. It is expected that the structure would find potential applications in active photonic devices, infrared imaging, detectors and tunable absorbers.